African Botanical Heritage for New Crop Development - Van Damme, Patrick; Termote, Céline (Afrika Focus, 2008)
The African continent is rather poor in plant biodiversity when compared to other continents on and around the equator. Nevertheless, lots of useful plant species have been domesticated from Sub-Sahara Africa material. Ethnobotanical research offers the possibility to collect information on the use and utility of wild plant species from traditional peoples often living in or close to a challenging natural environment. This type of information then allows us to find new candidates for domestication and subsequent crop development for income generation and increased food security. The case of Gnetum africanum illustrates the practical implications of developing a lesser-known species, and highlights the institutional problems that go together with niche crop development. The latter are subsequently presented and discussed in extenso, and solutions proposed in a second part of this review text. Key words: Ethnobotany, Domestication, Non-timber Forest Product, Value Chain, Marketing